2009
DOI: 10.1021/jp900328u
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Dye-Sensitized Solar Cell Based onoxo-Bacteriochlorin Sensitizers with Broadband Absorption Capability

Abstract: Two dye sensitizers, methyl trans-3 2 -carboxy-8-deethyl-7-ethyl-8-oxo-pyropheophorbide-a (BChlorin-1) and methyl trans-3 2 -carboxy-7-demethyl-8-methyl-7-oxo-pyropheophorbide-a (BChlorin-2), with stable bacteriochlorin skeletons were synthesized and applied to dye-sensitized solar cells. Both sensitizers absorb the light all over the visible region owing to partial saturation of the two pyrrole rings on the Q x transition dipole. When they were deposited on a TiO 2 film, the J-aggregates of the sensitizers ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 40 publications
3
65
0
Order By: Relevance
“…Thus, in order to have a significant effect, a decrease in J sc may be inevitable. 24,25 For the case of BMPPA, the increase of J sc is partly due to the positive shift of the quasi-Fermi level and, thus, the effect is expected for all dyes having relatively low LUMO levels. The drawback of the positive shift is the decreased V oc arising from a decreased difference between the conduction band edge and I À /I 3 À redox potential.…”
mentioning
confidence: 98%
“…Thus, in order to have a significant effect, a decrease in J sc may be inevitable. 24,25 For the case of BMPPA, the increase of J sc is partly due to the positive shift of the quasi-Fermi level and, thus, the effect is expected for all dyes having relatively low LUMO levels. The drawback of the positive shift is the decreased V oc arising from a decreased difference between the conduction band edge and I À /I 3 À redox potential.…”
mentioning
confidence: 98%
“…Tamiaki et al reported that compared to the blank sample, the CDCA coadsorbent enhanced the conversion efficiency from 6.2% to 6.6% at AM1.5, 100mW/cm 2 [73]. The same effect could be found when the PVA was used as a coadsorbent.…”
Section: Interface Modification Of the Coadsorbentmentioning
confidence: 82%
“…The commonly used efficient coadsorbents are chenodeoxycholic acid (CDCA) [73] and pivalic acid (PVA) [74]. Tamiaki et al reported that compared to the blank sample, the CDCA coadsorbent enhanced the conversion efficiency from 6.2% to 6.6% at AM1.5, 100mW/cm 2 [73].…”
Section: Interface Modification Of the Coadsorbentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compounds derived from naturally occurring chlorophylls are appealing as they are abundant, inexpensive in nature, and are feasible for molecular structure modification methods. [14][15][16][17] A large number of studies have focused on chlorin e6 due to its ease of synthesis from the precursor molecule, chlorophyll a. [18][19][20][21][22] In the construction of solar cells, co-adsorbents were used to minimize the strong aggregation effects caused by chlorin e6.…”
Section: Introductionmentioning
confidence: 99%